Greywater characterization of an Indian household and potential treatment for reuse - Pravin D. Patil; Vivek P. Bhange; Soniya S. Shende; Parnavi S. Ghorpade (Water-Energy Nexus, 2022)
Inadequate water supplies recall the environmental values of recovery and reuse of limited resources. One of the exciting opportunities in these circumstances is Grey water. Wastewater generated from household activities like bathing, kitchen sinks, washbasins, and laundry is classified as greywater. Inventing a pilot-scale greywater treatment system that treats in-house generated greywater and makes it reusable by assisting the untapped potential of physical methods of greywater purification was the main aim of this study. The study results from greywater samples' characterization from various sources in an Indian middle-class single household with four residents for six months. Moreover, the designing and analyzing of a treatment system applied to treat this in-house generated greywater was conducted. A filtration system with different filter layers was designed. It was found to have a chemical oxygen demand removal efficiency of 85.98%, biochemical oxygen demand removal efficiency of 86.28%, and total suspended solids removal efficiency of 94.44%. The filter system designed in this study describes improved removal efficiency in all respects and gives an idea of the reusability of in-house treated greywater. The study concludes that greywater can be recycled and reused for toilet flushing, gardening, car washing, and firefighting. This practice can also lead to a significant reduction in the consumption of freshwater.